(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the postoperative analgesic efficacy of continuous fascia iliaca compartment block (FICB) using 0.1% bupivacaine after total hip arthroplasty, and to record associated adverse effects. Methods: A prospective, randomized, controlled trial was conducted on 60 patients undergoing hip arthroplasty, randomized into two groups: MC group (n=30) received continuous FICB and TKD group (n=30) received continuous femoral nerve block. Both techniques used bupivacaine and were performed under ultrasound guidance. Results: Mean VAS scores at rest and during movement in both groups were <4 and significantly decreased compared with baseline (p<0.05). Between H1 and H10, the MC group had significantly lower VAS scores than the TKD group (p<0.05); from H12 to H48, the difference was not statistically significant (p>0.05). All patients had minimal motor blockade (Bromage score 0 or I); the proportion of Bromage I was lower in the MC group (43.3%) than in the TKD group (52.2%), with no significant difference. No adverse events such as pruritus, nausea, vomiting, or respiratory depression were observed. Conclusion: Continuous FICB under ultrasound guidance is an effective and safe method for postoperative analgesia in hip arthroplasty, providing good pain control with minimal motor blockade and few side effects.